Personal Branding Pendidik Tari dalam Pemberdayaan Komunitas Seni Sebagai Pewaris Budaya - Ghaniyyu Widiyaningrum, Alifiah (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
In the modern era, personal branding is increasingly important for individuals, including educators. Educators with strong personal branding can influence public perception of them and have a positive impact on the quality of education provided. In the context of arts education, particularly dance, educators serve not only as teachers but also as preservers and inheritors of culture. Therefore, dance educators are expected to have good personal branding so they can serve as role models for their students and the community. The current phenomenon is a lack of attention to the development of personal branding among dance educators. Many educators focus only on technical teaching skills, while aspects of strengthening their self-image and their role as agents of cultural preservation receive little attention. However, educators with strong personal branding can inspire their students to preserve traditional culture, which is increasingly marginalised by modernisation. Research indicates that effective personal branding strengthens the relationship between educators and students and increases the likelihood of greater appreciation for dance as part of cultural identity. This service is also related to the Sustainable Development Goals (SDGs), specifically Goal 4 (Quality Education) and Goal 11 (Cultural Engagement in Sustainable Communities) (1) The personal branding of dance educators can play a role in empowering the arts community by encouraging community involvement in cultural preservation. Qualitative research methods with a case study approach will be used to explore in depth how the personal branding of dance educators influences the empowerment of the arts community and cultural preservation.